Shift work that involves circadian disruption and breast cancer: a first application of chronobiological theory and the consequent challenges. - Fritschi, Lin; Valérie Groß, J.; Wild, U.; Heyworth, J.; Glass, D.; Erren, T. (2017)
Objectives: In 2007, the International Agency for Research on Cancer classified shift work involving circadian disruption (CD) as probably carcinogenic to humans. Circadian disruption could be conceptualised as the overlap of activity, such as work, with an individual's biological night. The latter can be approximated from a worker's chronotype (or morning/evening preference). Few previous studies have taken chronotype into account when assessing CD caused by shift work. Our objective was to test the hypothesis that women working during their biological night would be at increased risk of breast cancer. Methods: We used data from our case-control study of breast cancer to investigate associations between shift work involving CD and breast cancer risks. Previously, we had assumed that everyone working in jobs which involved work for two or more shifts between midnight and 05:00 hours was equally exposed to CD. In the present analyses, we reclassified as unexposed those who had a late chronotype in which their preferred bedtime was 2 hours after the end of their shift. RESULTS: Only 30 of 1385 night jobs changed classification and the overall finding (OR 1.17, 95%CI 0.98 to 1.41) was not different to the original finding when chronotype was not considered. Conclusions: We found virtually no difference between our new and old classifications of exposure. However, we were not able to calculate the total number of chronodisrupted shifts over a lifetime in order to assess dose and nor were we able to determine how many women were exposed to CD when doing shifts which began before midnight. Our first practical application highlights challenges for future chronobiology-based research.